Notoginsenoside R2 reduces Aβ25-35-induced neuronal apoptosis and inflammation via miR-27a/SOX8/β-catenin axis. (December 2021) - Hu, Yueqiang; Wu, Lin; Jiang, Lingfei; Liang, Ni; Zhu, Xiaomin; He, Qianchao; Qin, Hongling; Chen, Wei
Background: Alzheimer's disease (AD) has affected numerous elderly individuals worldwide. Panax notoginseng has been shown to ameliorate AD symptoms, and notoginsenoside R2 is a key saponin identified in this plant.Purpose: In the current study, we aimed to explore whether notoginsenoside R2 could improve the prognosis of AD.Methods: Herein, primary rat cortical neurons were isolated and they were treated with amyloid beta-peptide (A β ) 25–35 oligomers. Cellular apoptosis was examined via flow cytometry and Western blotting. miR-27a and SOX8 mRNA expression levels were quantified by quantitative reverse transcription-polymerase chain reaction. Furthermore, the interaction between miR-27a and SOX8 was investigated by utilizing a dual-luciferase reporter assay. Finally, an AD mouse model was established to validate the in vitro findings.Results: Notoginsenoside R2 alleviated A β 25-35-triggered neuronal apoptosis and inflammation. During this process, miR-27a expression was decreased by notoginsenoside R2, and miR-27a negatively modulated SOX8 expression. Furthermore, activation of SOX8 upregulated β -catenin expression, thus suppressing apoptosis and neuroinflammation.Conclusions: Our animal experiments revealed that notoginsenoside R2 enhanced the cognitive function of AD mice and inhibited neuronal apoptosis. Notoginsenoside R2 ameliorated AD symptoms by reducing neuronal apoptosis and inflammation, thus suggesting a novel direction for AD pharmacotherapy.